Sosialisasi dan Edukasi Pemberian Makanan Tambahan Cookies Daun Kelor dan Pisang untuk Mengurangi Prevalensi Anemia di Puskesmas Sibiru-Biru - Gultom, Yohana Tetty; Lisnawati Tumanggor (Universitas Methodist Indonesia, 2025)
Anemia in pregnant women is a nutritional problem that can reduce immune function, impair children’s cognitive and motor development, and increase the risk of pregnancy and childbirth complications. At Puskesmas Sibiru-biru, Deli Serdang Regency, a community service program aimed to improve mothers’ knowledge about anemia and its prevention by providing them with supplemental foods made from local ingredients, such as moringa leaf and banana cookies. A total of 30 mothers with children aged 1 to 5 years actively participated in counseling, discussions, and hands-on cookie-making activities. The results showed that participants’ knowledge and interest increased through instruction combined with practical exercises. Additionally, the cookies were well accepted as a nutritious alternative for supplementary food. By utilizing local foods, this program helps families prevent anemia.